A Phase I, Randomized, Single-Dose Study to Evaluate the Biosimilarity of QL1206 to Denosumab Among Chinese Healthy Subjects - Hong Zhang; Min Wu; Xiaoxue Zhu; Cuiyun Li; Xiaojiao Li; Jixuan Sun; Chengjiao Liu; Quan Liu; Wei Wei; Junqi Niu; Yanhua Ding (Frontiers Media S.A., 2020)
ObjectiveThis study was conducted to explore the tolerance, variability, pharmacokinetics (PK), and pharmacodynamics (PD) of denosumab biosimilar (QL1206) in healthy Chinese subjects.MethodsThis is a randomized, double-blind, two-arm, parallel study performed to examine the bioequivalence of denosumab biosimilar, QL1206, with that of Xgeva® (Denosumab) as a reference drug. A single dose of 120 mg/kg of the denosumab biosimilar or Xgeva® was administered to the subjects, who were followed up for 134 days.ResultsSimilar PK properties as those of Xgeva® were exhibited by QL1206. When compared to QL1206 with Xgeva®, the 90% confidence intervals of the ratios for Cmax, AUC0-t, and AUC0-∞ were observed to be within 80-125%. The inter-subject variability (inter-CV) ranged from 29% to 39.5%. Six and three subjects in the QL1206 and Xgeva® groups were found to be positive for the ADA and negative for the NAb, respectively. The CTX1 concentration-time profiles appeared similar (about 80% decrease from 48 hours to134 days) between the QL1206 and Xgeva® groups. Adverse events (AEs) were observed in 92.6% and 93.4% of subjects in the QL1206 and Xgeva® groups, respectively. Reduction in blood calcium level was found to be the most common AE recorded, with an incidence of 72.8% versus 72.4% in the QL1206 and Xgeva® groups, respectively.ConclusionSimilar PK and PD characteristics were exhibited by QL1206 as compared to those of Xgeva®. The inter-CV was slightly large. The safety profiles of denosumab biosimilars and Xgeva® were found to be similar.